Investigating the role of entrepreneurial skills in fostering desire among university undergraduates:A Conceptual paper - Ab Wahab, Nur Yuhainis; Abu Hassan, Mohamad Hanif; Ahmad Sabri, Nurul Syazwani; Abd Halim, Siti Noorjannah; Zakaria, Muhammad Fadzly; Zamri, Nur Aisyatul Azra; Abdullah, Syaqirah (International Business Education Journal, 2025)
Entrepreneurship is often seen as an attractive career path for university students; however, the extent of their desire to pursue it remains a topic of inquiry. Although numerous studies have explored this subject, the findings have been inconsistent. This study will assess the level of entrepreneurial desire among university students, with a specific focus on the role of entrepreneurial skills. A quantitative approach will be adopted, with data to be collected through questionnaire surveys administered to 376 undergraduate students enrolled in Bachelor of Education programs at Universiti Pendidikan Sultan Idris (UPSI), covering semesters one through eight. The data will be analyzed using descriptive statistics and inferential methods, including Pearson’s correlation and multiple regression analysis. The findings will offer valuable insights for policymakers, universities, and the Ministry of Education, highlighting the need to implement effective strategies and programs to nurture entrepreneurship among university students. Ultimately, this study will be important because it will provide a foundational understanding of how entrepreneurial skills influence students’ desire to pursue entrepreneurship, which will be crucial for addressing graduate unemployment. By informing universities and policymakers, it will help shape more effective educational strategies that empower students to become future job creators.